Background conductivity independent counter flow preconcentration method for capillary electrophoresis. Issue 21 (15th May 2017) - Koenka, Israel Joel; Hauser, Peter C.
Abstract: A preconcentration method for anions is presented, which relies on a trap created by applying an electric field against a hydrodynamic flow of the sample. The trapping zone is created in front of a cation exchange membrane that allows the isolation of the electrode and thus prevents any interference by electrolysis products. Preconcentration factors of up to 20 were demonstrated for nitrate and formate as model analyte ions and were linearly related to the sample volume passed through the trap. A discrimination between the ions was found possible by adjustment of the hydrodynamic flow velocity. The method was also found to be suitable for the preconcentration of an anion (nitrate at 100 μM) in presence of a second anion at a very high concentration (50 mM formate). The detection limits for the four anions chloride, nitrate, perchlorate, and formate could be lowered from 4, 4.3, 4.2, and 7.2 μM obtained without trapping respectively to 127, 142, 139, and 451 nM with trapping.